Orally co-Infected Aedes albopictus from La Reunion Island, Indian Ocean, can deliver both dengue and chikungunya infectious viral particles in their saliva. - Marie Vazeille; Laurence Mousson; Estelle Martin; Anna-Bella Failloux (Public Library of Science (PLoS), 2010)
BACKGROUND: First described in humans in 1964, reports of co-infections with dengue (DENV) and chikungunya (CHIKV) viruses are increasing, particularly after the emergence of chikungunya (CHIK) in the Indian Ocean in 2005-2006 due to a new variant highly transmitted by Aedes albopictus. In this geographic area, a dengue (DEN) outbreak transmitted by Ae. albopictus took place shortly before the emergence of CHIK and co-infections were reported in patients. A co-infection in humans can occur following the bite of two mosquitoes infected with one virus or to the bite of a mosquito infected with two viruses. Co-infections in mosquitoes have never been demonstrated in the field or in the laboratory. Thus, we question about the ability of a mosquito to deliver infectious particles of two different viruses through the female saliva. METHODOLOGY/PRINCIPAL FINDINGS: We orally exposed Ae. albopictus from La Reunion Island with DENV-1 and CHIKV isolated respectively during the 2004-2005 and the 2005-2006 outbreaks on this same island. We were able to show that Ae. albopictus could disseminate both viruses and deliver both infectious viral particles concomitantly in its saliva. We also succeeded in inducing a secondary infection with CHIKV in mosquitoes previously inoculated with DENV-1. CONCLUSIONS/SIGNIFICANCE: In this study, we underline the ability of Ae. albopictus to be orally co-infected with two different arboviruses and furthermore, its capacity to deliver concomitantly infectious particles of CHIKV and DENV in saliva. This finding is of particular concern as Ae. albopictus is still expanding its geographical range in the tropical as well as in the temperate regions. Further studies are needed to try to elucidate the molecular/cellular basis of this phenomenon.